2008
DOI: 10.1021/nl802696f
|View full text |Cite
|
Sign up to set email alerts
|

Blinking Statistics Correlated with Nanoparticle Number

Abstract: We report fluorescence of single semiconductor nanorods (NRs) and few-NR clusters, correlated with transmission electron microscopy for direct determination of the number of NRs present in a single fluorescent source. For samples drop-cast from dilute solutions, we show that the majority of the blinking sources (approximately 75%) are individual NRs while the remaining sources are small clusters consisting of up to 15 NRs. Clusters containing two or three NRs exhibit intermittent fluorescence intensity traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
68
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 24 publications
5
68
1
Order By: Relevance
“…3a). Although it has been shown that blinking statistics are threshold dependent when the threshold is varied significantly 16,20,24 , our analysis confirms that the trends reported here hold for a wide range of reasonable thresholds (see detailed analysis of on-times for different thresholds in Methods). All results reported in the main paper were determined using a threshold of m dark + 7σ dark (red line in Fig.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…3a). Although it has been shown that blinking statistics are threshold dependent when the threshold is varied significantly 16,20,24 , our analysis confirms that the trends reported here hold for a wide range of reasonable thresholds (see detailed analysis of on-times for different thresholds in Methods). All results reported in the main paper were determined using a threshold of m dark + 7σ dark (red line in Fig.…”
Section: Resultssupporting
confidence: 86%
“…2) by setting a threshold distinguishing the fluorescence intensity as 'on' or 'off, ' digitizing the trace according to that threshold, and then converting the digitized trace to sequences of 'on' and 'off ' times 6,20 . We identify the threshold above which a fluorescence signal is considered 'on' using the mean, m dark , and standard deviation, σ dark , of the background intensity measured from a nearby bare region of the substrate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations